PREVALENCE OF TRICHOMONIASIS IN ASYMPTOMATIC PREGNANT WOMEN POPULATION IN BANDUNG, WEST JAVA, INDONESIA - Achdiat, Pati Aji; Dwiyana, Reiva Farah; Feriza, Vina; Rowawi, Rasmia; Effendi, Rendy Ariezal; Suwarsa, Oki; Gunawan, Hendra (Indonesian Journal of Tropical and Infectious Disease, 2019)
About 81% of pregnant women with trichomoniasis are asymptomatic, while trichomoniasis in pregnant women can increase the risk of complications, include premature rupture of membranes, preterm birth, and babies with low birth weight. Trichomoniasis can also increase the risk of other sexually transmitted infections (STIs) and human immunodeficiency virus (HIV) transmission. Trichomoniasis case in pregnant women could be influenced by demographic characteristics,, the sexual behavior, and also the diagnostic method used. Until now, there is no data about prevalence of trichomoniasis in pregnant women in Indonesia. The aim of this research was to determine the prevalence of trichomoniasis in pregnant women in Bandung, West Java, Indonesia. A descriptive cross-sectional study was performed in December 2016 until January 2017. The study participants were 50 pregnant women who visit antenatal care to Obstetric and Gynecology Clinic of 'Rumah Sakit Khusus Ibu dan Anak Kota Bandung', and meet the inclusion and exclusion criteria, through consecutive sampling. The study participants had a history taking, venereological examination, and Trichomonas rapid test from vaginal swabs. Trichomoniasis in this study was diagnosed based on Trichomonas rapid test, a test that uses color immunochromatographic, capillary flow, dipstick technology, and has high sensitivity and specificity in diagnosing trichomoniasis. Almost all participants in this study were low risk pregnant women to have STI based on demographic characteristics and sexual behaviour. The positive Trichomonas rapid test result was found from one of 50 study participants. In conclusion, prevalence of trichomoniasis in pregnant women in Bandung was 2%. Trichomoniasis case in low-risk pregnant women population is still found.